Financing from Family and Friends - Lee, Samuel; Persson, Petra (Review of Financial Studies, 2016)
Financing from family and friends is the predominant type of informal finance. This paper proposes a theory that reconciles two seemingly paradoxical traits of this form of finance, namely, it is often provided at negative prices but nevertheless eschewed by borrowers. A central prediction is that such finance, while breeding trust, deters risk taking. Demand is thus constrained: entrepreneurs may forgo risky investment rather than finance it through family and friends. Formal finance is valuable precisely because it is regulated only by contract. The highlighted trade-offs between formal and informal finance are potentially relevant for the provision of microventure capital.